THE ECONOMIC RISK IN TRADING COMPANIES’ VALUATION - Muntean, Mircea; Bucur, Iulia Andreea; Muntean, Andrei (Studies and Scientific Researches. Economics Edition, 2014)
The negative influence of internal and external factors on the enterprise’s operating activity may lead to the realization of losses and economic-financial imbalance of the enterprise. Such situation leads to the economic risk, which can be avoided by diagnosis analysis. The manifestation of the economic risk has repercussions in: obtaining profit from operating activities, the maximization of the enterprise’s value and the increase of the market share. The operational risk can be detected by the method of forecast analysis “cost-volume-profit” or via coefficient of lever exploitation. This paper aims, on the basis of the information of a commerce company, to reveal the influence of risk in assessing the enterprise, as well as the possibilities to maximize its value and the increase in economic and financial performance in a competitive environment. The results of the research demonstrate the impact of the circulating expenditure structure on the enterprise’s financial results, as well as on equity.